Science and fiction in Argentina - Campanna, Pablo (Universidad Nacional del Litoral, 2018)
Despite having some remarkable authors, science fiction is a genre that has never come to take root in Argentinean literature. At countries with greater industrial development science fiction was useful in awakening vocations for science and technology. In Argentina, the relationship between science and science-fiction has been different, including those authors that have scientific training. Very different was the project of the magazine Más allá that introduced the genre in the fifties, and made the greatest effort to open dialogue between the «two cultures» and integrating them.